1995
DOI: 10.1136/jnnp.58.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory postural adjustments during self inflicted and predictable perturbations in Parkinson's disease.

Abstract: This study investigated the relation between impaired anticipatory postural adjustments and bradykinesia in Parkinson's disease. Patients with Parkinson's disease and age matched controls stood on a platform. In one series of experiments, they performed fast, discrete shoulder flexion or extension movements. In another series, they were required to press a trigger with the right thumb and thus to release a load that was suspended from a bar which they were holding in front of them in extended arms. One more se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(81 citation statements)
references
References 30 publications
1
72
1
7
Order By: Relevance
“…This hypothesis was based on clinical speculation (Morris 2000;Morris et al, 1997), in addition to the literature which has demonstrated impaired anticipatory postural control during arm movements while standing in PD subjects (Latash et al 1994;Rogers et al 1987;Traub et al 1980). Furthermore, several studies have shown altered function of the supplementary motor area in PD due to its indirect connections with the basal ganglia (Cunnington et al 1996;Grafton et al 1995).…”
Section: Altered Movement Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was based on clinical speculation (Morris 2000;Morris et al, 1997), in addition to the literature which has demonstrated impaired anticipatory postural control during arm movements while standing in PD subjects (Latash et al 1994;Rogers et al 1987;Traub et al 1980). Furthermore, several studies have shown altered function of the supplementary motor area in PD due to its indirect connections with the basal ganglia (Cunnington et al 1996;Grafton et al 1995).…”
Section: Altered Movement Strategymentioning
confidence: 99%
“…It has been speculated that the inability to rise from a chair in persons with PD may be a result of altered anticipatory postural control and consequently a failure to bring the COM adequately forward over the feet prior to the lift-off of the buttocks from the chair (Morris 2000;Morris et al 1997). Such hypotheses have been fueled by reports of altered anticipatory postural control during tasks such as arm movements while standing in PD subjects (Latash et al 1994;Rogers et al 1987;Traub et al 1980), in addition to altered supplementary motor area function in PD, which has been linked to the performance of preparatory postural control during tasks such as finger movements (Cunnington et al 1996). However, no study has yet quantified the movement strategies used by individuals with PD to rise from a chair.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the last few decades, it has been found that the brainstem reticular formation 28) , cerebellum 29,30) , basal ganglia 31) , and cerebral cortex 32) play important roles in the control of dynamic postural balance. Recently, the role of the motor cortex in controlling forearm posture has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the results of the present study indicate that, in both pre-and post-training, wearing unstable shoes leads the postural control system to rely more on reciprocal activation than on co-activation to compensate for the decreased stability compared to barefoot. This has been demonstrated to be more efficient and accurate, but also more challenging for the postural control system (Aruin & Almeida, 1997;Friedli et al, 1984;Garland et al, 1997;Hogan, 1984;Hong et al, 1994;Latash et al, 1995;Massion et al, 1999), and it has been observed also in compensatory postural adjustments in response to an external perturbation (Sousa, et al, 2013a;Sousa, et al, 2014). These findings demonstrate that wearing unstable shoes is more demanding in terms of postural control than barefoot, but lead to a higher efficiency and accuracy in postural commands.…”
Section: Standing With Unstable Shoes Is More Demanding In Terms Of Pmentioning
confidence: 99%